A note on product-convolution for generalized subexponential distributions - Konstantinides, Dimitrios; Leipus, Remigijus; Šiaulys, Jonas (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, we consider the stability property of the class of generalized subexponential distributions with respect to product-convolution. Assuming that the primary distribution is in the class of generalized subexponential distributions, we find conditions for the second distribution in order that their product-convolution belongs to the class of generalized subexponential distributions as well. The similar problem for the class of generalized subexponential positively decreasing-tailed distributions is considered.
Keywords: product-convolution; subexponential distribution; generalized subexponential distribution